Toward a multiroute model of number processing: impaired number transcoding with preserved calculation skills. - Cipolotti, Lisa; Butterworth, Brian (Journal of Experimental Psychology. General, 1995)
This article describes a patient (S.A.M.), suffering from a progressive neurological degenerative condition of unknown origin, who showed a severe difficulty in number transcoding tasks. S.A.M. could recognize and understand arabic numerals and written number names, but he could neither read them aloud nor write them. However, he had a well maintained ability to perform oral and written calculations. The striking pattern of performance observed in S.A.M. suggests that deficits affecting the ability to produce arabic or verbal numerals can be specific to particular task demands. This observation cannot be easily accommodated by current models of numerical processing. A new multiroute model for numerical processing is proposed to account for S.A.M.'s pattern of performance. This model adds asemantic transcoding pathways to the semantic processing mechanisms proposed by the M. McCloskey model. Reprinted by permission of the publisher.